Young asteroidal fluid activity revealed by absolute age from apatite in carbonaceous chondrite - Zhang, Ai-Cheng (Nat Commun, 2016)
Chondritic meteorites, consisting of the materials that have formed in the early solar system (ESS), have been affected by late thermal events and fluid activity to various degrees. Determining the timing of fluid activity in ESS is of fundamental importance for understanding the nature, formation, evolution and significance of fluid activity in ESS. Previous investigations have determined the relative ages of fluid activity with short-lived isotope systematics. Here we report an absolute (207)Pb/(206)Pb isochron age (4,450±50 Ma) of apatite from Dar al Gani (DaG) 978, a type ∼3.5, ungrouped carbonaceous chondrite. The petrographic, mineralogical and geochemical features suggest that the apatite in DaG 978 should have formed during metamorphism in the presence of a fluid. Therefore, the apatite age represents an absolute age for fluid activity in an asteroidal setting. An impact event could have provided the heat to activate this young fluid activity in ESS.